2021
DOI: 10.1177/20503121211045247
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity costs of attending surgical clinic appointments and experiences with telemedicine for follow-up care

Abstract: Objectives: Telemedicine has been rapidly implemented in orthopedics during the coronavirus (COVID-19) pandemic. The purpose of this study was to quantify opportunity costs for patients attending typical in-person appointments and understand their perceptions of telemedicine for follow-up care. Methods: A cross-sectional study was performed by surveying patients who had elective orthopedic surgery and attended at least one in-person and one phone call appointment. The survey assessed opportunity costs associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…To address this, many clinics will overbook appointments to retain productivity in the setting of missed visits; however, there are increased opportunity costs to patients through prolonged queues in clinic and decreased patient satisfaction, which may further exacerbate future no-show rates. 21,22 Distance and Travel Time Distance from care is thought to have a negative effect on patient care and follow-up across many healthcare specialties. 20,23,24 Despite this, few studies have cited distance as a risk factor for orthopaedic surgery patients in not attending their follow-up appointments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, many clinics will overbook appointments to retain productivity in the setting of missed visits; however, there are increased opportunity costs to patients through prolonged queues in clinic and decreased patient satisfaction, which may further exacerbate future no-show rates. 21,22 Distance and Travel Time Distance from care is thought to have a negative effect on patient care and follow-up across many healthcare specialties. 20,23,24 Despite this, few studies have cited distance as a risk factor for orthopaedic surgery patients in not attending their follow-up appointments.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Implementation of telehealth follow-up appointments may increase patient commitment to care, but this may not be feasible in all clinics. 22 Alternatively, telemedicine visits could be offered exclusively to patients who are at a higher risk of missing a postoperative appointment. 21 Telehealth follow-up appointments would be suitable for addressing pain, wound healing, and mobility concerns.…”
Section: Strategies For Improvementmentioning
confidence: 99%
“…For some practice settings there will be an upfront cost to acquire equipment for telehealth as well as a period of lower efficiency while transitioning to a different model of patient visits, but there is likely to be an eventual net cost savings 32 . Traditional visits carry a large opportunity cost in terms of missed work, travel time and missed recreation for patients 33 . Based on the amount of time spent traveling and waiting to see a physician, telehealth has the potential to decrease these costs dramatically 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of VFC increased remote delivery of care, which has proven to be an efficient, cost-effective and satisfactory alternative to face-to-face care (Ekeland et al., 2010; Graham et al., 2021; Haider et al., 2022; Lee et al., 2021; Thatcher et al., 2021). Other studies on VFC protocols have reported similar results (Brogan et al., 2017; Davey et al., 2020; Dunkerley et al., 2020).…”
Section: Discussionmentioning
confidence: 99%